Growth and equity in Finland - Markus Jäntti; Juho Saari; Juhana Vartiainen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper reviews Finnish economic history during the `long' twentieth century with a special emphasis on policies for equity and growth. We argue that Finland developed from a poor, vulnerable, and conflict-prone country to a modern economy in part through policies geared at both growth and equity, such as land reform and compulsory schooling. The state participated in economic activity both indirectly and directly in the post-war period, implementing many social policy reforms that facilitated the functioning of the labour market and led to greater equity. Centralised collective bargaining was just one of the many means through which central government intervened in the economy. Both the long-run growth record and the equality of different kinds of economic outcomes are fairly positive. This suggests that facilitating economic growth through such policies that further more equitable outcomes may at least in the case of Finland have met with some success.
Keywords: J50; N33; N34; O52; 330; economic growth; income distribution; labour unions; schooling; public policy; Wirtschaftsgeschichte; Wirtschaftswachstum; Einkommensverteilung; Sozialstaat; Finnland